Kidney failure screening in the general population of rural Africa - Bah, Alpha Oumar; Balde, Mamadou Cellou; Kimso, Oumou; Kaba, Mohamed Lamine; Ngammie, Christelle (African Journal of Nephrology, 2015)
Kidney failure is a silently progressive disease too often unknown to the patients. The objective of this study was to assess the impact of kidney disease in Conakry so as to develop strategies for early detection and prevention. This was a descriptive-type prospective study carried out over six months, from January 31 to July 31, 2012. The study was carried out in two areas: In health facilities where the population were at a higher risk of developing kidney disease (diabetes, uropathies, infectious diseases and HIV, hypertension and cardiovascular disease), and in an apparently healthy population. In the study we included black subjects hospitalised in different targeted wards, as well as fully active apparently healthy subjects of the general population. Renal function was assessed with the simplified MDRD formula. Data collection included clinical parameters: Blood pressure, weight, height and blood laboratory parameters (creatinine, glucose) and urine (urine dipstick, 24h quantitative proteinuria). One hundred and ninety-nine patients were selected for the study: 117 men and 82 women ageing from 20 to 90 years. The prevalence of renal failure was 59% in the population at risk, with 53.3% of men and 16% in apparently healthy population with 60% of men with a statistically significant difference: p = 0.00000001. Proteinuria was observed in 86 patients in the population at risk against 19 in the healthy population.